Trouble next door - English, Karen (English, Karen. Carver chronicles, 2016)
"Third grader Calvin is dealing with his next door neighbors moving away--and the school bully moving in. Meanwhile, competition at the school science fair is heating up, and Calvin must decide what to do when his data doesn't prove his theory"--